The achiote Bixa orellana L. as productive possible alternative to Meta Department (Revista Sistemas de Producción Agroecológicos, 2014)
An analysis of Bixa orellana L. achiote productive as possible alternative for industrial development Meta was performed by collecting information on this plant research and the experiences of countries like Peru, in which the annatto is one of the main export products. First, a framework focused on phenology, climatic requirements, agronomic, processing and markets was generated. Was found that this amazon species is distributed in 19 of the 32 departments, fits chemically poor soils, provided they present good physical condition (sandy loam texture) for root development, the best yields are achieved at lower altitudes 800 m, is a good user of water and to prevent pathological level seed problems, it is important not to have relative humidities above 80%. The main insects that cause damage are sucking bugs as (Leptoglossus zonatus) chewing like ants (Atta mexicana) and capsule borer (Milgithea melanoleuca). The main pathogens that may affect the crop are fungi Oidium bixaea, Collectotrichum gloeosporioides, Crinipellis pernicious, Fusarium sp. and Cercospora bixae. The capsule production per hectare can vary depending on the area and especially crop management, finding productions per hectare greater than 5 tons and less than 1 ton. In conclusion, the increasing global demand for natural dyes, the Meta offer agroclimatic, proximity to the capital as the main market for the trading of this product and the development of the productive chain of aromatic and medicinal plants are opportunities for the economic development of this plant.
Keywords: achiote; Bixa orellana; natural dye